Renal osteodystrophy in the oral and maxillofacial region: a case report and literature review - Demenech, Laura Marina; Cepeda, Isadora Vilas Bôas; Orcina, Bernardo da Fonseca; Nachtigal, Clarissa Fôlha; Langlois, Caroline de Oliveira; Torriani, Marcos Antonio; Fogaça, Antonio Cesar Manentti; Etges, Adriana (Journal of Oral Diagnosis, 2025)
This study presents a case report of a patient with chronic kidney disease (CKD) with secondary hyperparathyroidism and the presence of manifestations in the oral-maxillofacial complex with Renal osteodystrophy (ROD). Also, a literature review in the PubMed was carried out using the MeSH Terms descriptors (((jaws) AND (treatment)) AND (secondary hyperparathyroidism)) AND (case reports). The search was limited to articles written in English and published in the last 10 years. Also, this article presented the clinical case of a 49- year-old caucasian female patient, with volumetric increase in jaws after dental extraction. The patient reported having CKD for 10 years. Clinical examination of the patient revealed enlargement of the alveolar bone ridge in the maxilla and mandible. The maxilla showed an evident loss of palatal concavity, and the mandible loss of space at the bottom of the vestibular groove. The diagnosis of ROD was consolidated after the analysis of imaging tests, laboratory tests and histopathological evaluation of the bone tissue. The manifestation of systemic diseases in the face demands a systemic look, to establish treatments with the best prognosis. We reinforce the need for multidisciplinary work for the correct diagnosis and management of patients with systemic diseases.